‘I can’t see you any more’: A phenomenology of political Facebook unfriending - John, Nicholas; Gal, Noam (AoIR Selected Papers of Internet Research, 2016)
This study explores the phenomenology of politically motivated Facebook unfriending and is based on semi-structured in-depth interviews with 18 Jewish Israeli Facebook users who unfriended at least one Facebook friend during the Israel-Gaza conflict of 2014. This research contributes to two main theoretical concerns. The first is the emerging study of disconnectivity, and particularly unfriending. The second relates to the potential for social media to serve as platforms for political discussion. We ask: Is political unfriending part of a trend towards polarization, whereby we screen out political views we find unpalatable? Is it a normative statement about the acceptable limits of discourse? Or is it an apolitical act of consumer choice, more akin to changing channels on the TV than voting in an election? Two main groups of findings emerge from analysis of the interviews. First, unfriending can be conceptualized as metacommunicative. Through unfriending, users are saying something about unacceptable types of talk. Second, all of the interviewees said they unfriended someone because they simply couldn’t deal with seeing that person’s content any more. This was very often accompanied by metaphors of cleanliness. Through unfriending, Facebook users shape both the content and the style of expression to which they are exposed on their feed. Unfriending is thus conceptualized as a kind of boundary maintenance. However, unlike work that relates boundary maintenance to privacy and looks at what information we allow out, here we see unfriending as a mechanism for controlling what we allow in within a context of networked sociability.